ChemInform Abstract: Olefin Isomerization and Hydrosilylation Catalysis by Lewis Acidic Organofluorophosphonium Salts. Issue 22 (3rd June 2014) - Perez, Manuel; Hounjet, Lindsay J.; Caputo, Christopher B.; Dobrovetsky, Roman; Stephan, Douglas W.
Abstract In addition to the hydrosilylation reaction, the catalyst can also be used for the isomerization of alkenes under similar conditions (without a silane), e.g. 1‐hexene is isomerized to an E/Z mixture of 2‐hexene along with small amounts of polymerization products.